(3GdJMbjb dCMGOjK GdJYdjbs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3djS MOjKkG HTF hbGd GdOGQbWfi gh eJQhc s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg bGd QShd Gddg Udi Gddg Ydjg hSde UObI GdaWQ Yf cd UZjQ hcHjQ PcQ hGfKi fUa UGY ef JeQ ChUGY ef TYjQ , WQjb BNQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3Gdabg GdMfHdjs